Training on Making Aromatherapy Candles for Body Health for Housewives in the Joso Triyagan Area RT 01 / RW 01, Mojolaban, Sukoharjo. - Fajar Alam Putra; Widiyono Widiyono; Atik Aryani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Mosquitoes are one of the causes of community problems because they can cause various diseases and interfere with comfort. Mosquitoes can be caused due to lack of environmental hygiene in the community. Nowadays, many people are afraid to use ready-made mosquito repellent products that have been made and issued by certain factories or industries. The chemical content contained in these preparations is the reason why people are looking for other alternatives to make mosquito repellents using natural ingredients that are safer. One of the efforts to prevent and control mosquito attacks is to use air fresheners in the form of aromatherapy gels and candles. Making aromatherapy candles is quite easy and the ingredients are very affordable so that people can make their own. The purpose of this activity is to increase public awareness of the importance of maintaining a clean environment to create health for the family as well as training in making aromatherapy candles with natural ingredients, producing products that can be used alone or developed into a home industry. This activity was carried out by providing environmental hygiene education and workshops on making aromatherapy candles as an alternative to mosquito repellent. The results obtained are an increase in people's understanding of environmental hygiene. In addition, aromatherapy has benefits for body health and then aromatherapy candles are produced as mosquito repellents whose production can be developed on a household industrial scale in the Joso Triyagan area RT 01 / RW 01, Mojolaban, Sukoharjo.